Alcohol induced modifications in adipose tissue: A potential risk factor for metabolic imbalance? - Monopoli, Lucas (2024)
Adipose tissue (AT) has a remarkable ability to adjust its size and function in response to various internal and external signals, such as nutritional status and temperature. The regulatory circuits governing fuel storage and oxidation in white adipocytes and thermogenic in brown/beige adipocytes, are crucial for maintaining systemic energy homeostasis. However, when these pathways become dysregulated, it can lead to metabolic disorders and AT dysfunction, including obesity. This study aimed to investigate the effect of alcohol intake on the metabolic function of AT. Adult male mice (Mus musculus, CrlFcen) were exposed to 15% (v/v) ethanol in drinking water ad libitum for 12 days, followed by two days on water only. Males were euthanized and dissected to obtain AT from subcutaneous, gonadal, peri-retroperitoneal and brown adipose tissue (BAT) depots. Histological examination of the samples was performed after fixation and staining (H&E). AT lysates underwent Western blot analysis for lipase expression (HSL, ATGL) and adipocyte markers (FABP4, CAV-1, UCP-1, Adiponectin). Alcohol consumption significantly increased ATGL and adiponectin expression in subcutaneous adipose tissue (p=0.05), HSL expression in BAT (p=0.005) and showed a tendency to increase HSL in retroperitoneal AT(p=0.07). UCP1 expression levels did not show any difference between the groups in BAT depots. Histological analysis revealed a tendency to decrease the number of vacuoles in BAT and the vacuole area increased in gonadal tissue (p=0.02) with treatment, suggesting triglyceride storage. We also evaluated the levels of glucose and other metabolites in serum to analyzed metabolic status of the mice. In sum, alcohol consumption induces significant alterations in adipose tissue metabolism and morphology. These results suggest that alcohol intake may influence fat storage and energy homeostasis, potentially altering the balance between white and brown adipose tissue, which could have implications for metabolic health.